Development of social media addiction scale for COVID-19 pandemic (SMACOP) - Lim, KQ; Zulkifli NA,; Karupiah G,; Miundy P,; Ng, Chong Guan; Low, SY (Pusat Perubatan Universiti Kebangsaan Malaysia, 2021)
The current COVID-19 pandemic and ‘new normal’ has resulted in much distress worldwide. Social media currently plays an essential role in information gathering. Thus, time spent on social media has increased drastically, further increasing the risk for internet-related addictions, such as social media addiction. This study aimed to develop a COVID-19-related measure of social media addiction based on the Bergen Social Media Addiction Scale (BSMAS) in order to aid in the identification and evaluation of at-risk individuals. Social Media Addiction Scale for COVID-19 Pandemic (SMACOP) was adapted from BSMAS to fit the context of COVID-19 and pilot tested on 20 individuals. A total of 80 participants were subsequently recruited through convenience sampling from the general public of a public university in Malaysia, comprising of patients’ family, visitors, or hospital staff. Construct validity was assessed using the Insomnia Severity Index (ISI), Generalized Anxiety Disorder 7 (GAD7) and Patient Health Questionnaire (PHQ9). A two-factor structure was found for SMACOP, comprising of the factors ‘Desire’ and ‘Distress’. SMACOP shows good internal consistency (α = 0.64) and validity. SMACOP scores were positively correlated with the PHQ9, GAD7, and ISI (p<.01). SMACOP is a psychometrically valid instrument with high internal consistency, which is especially useful during this time in assessing social media addiction in relevance to COVID-19.